Breast Fibroadenoma Association: Hodgkin’s Disease and Bilateral Inflammatory Breast Cancer: Aetiopathogenic considerations regarding a case - Viola Alles, Alberto; Armand Ugón, Alfredo; Matteucci, Pablo; De Los Santos, Julio (Cirugía del Uruguay, 1982)
One case of a 42 year old woman wlth such an association is presented. Sorne aspects of the oncogenesis are discussed, emphasizing the appearence of a second tumor in patients with a Hodgkin disease and the relationship between fibroadenoma and breast cancer.